Perspectives on the Application of Biosensors for the Early Detection of Oral Cancer - Sanket Naresh Nagdeve; Baviththira Suganthan; Ramaraja P. Ramasamy (Sensors)
Oral cancer continues to cause profound suffering and is associated with high mortality rates. Early detection techniques are crucial in enhancing patient outcomes. This review paper thoroughly evaluates the significance of biomarkers and recent advancements in oral cancer detection, emphasizing cutting-edge electrochemical methods. The paper provides an epidemiological and etiological overview, outlining its clinical importance and reviewing the current state of the art in detection methods. Despite considerable progress, conventional methods exhibit limitations such as invasiveness, long wait times, and a lack of accuracy, creating a critical need for more robust technologies. This review emphasizes the significance of oral cancer biomarkers, which are considered promising cues for early detection, facilitating the development of innovative biosensing technologies. This review seeks to illuminate the recent advances in early detection and precision diagnostics, along with the usage of artificial intelligence strategies, ultimately contributing to significant progress in the battle against oral cancer.